2020
DOI: 10.3390/antiox9121305
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Redox Profiles of the Serum and Aqueous Humor in Patients with Primary Open-Angle Glaucoma and Exfoliation Glaucoma

Abstract: Oxidative stress is thought to play a significant role in the development of glaucoma. However, the association between systemic and local oxidative stresses in different types of glaucoma has not been assessed fully. The current study compared the redox status in the aqueous humor (AH) and blood samples among eyes with primary open-angle glaucoma (POAG), exfoliation glaucoma (EXG), and non-glaucomatous controls to evaluate the relationship among systemic redox status, intraocular oxidative stress, and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
(69 reference statements)
1
10
1
2
Order By: Relevance
“…Among these studies, some changes were found to be common in several reports and share similar or overlapping metabolic pathways. For instance, significant upregulation of the metabolites in responding to oxidative stress was reported in both studies by Buisset et al (2019) and Takayanagi et al (2020) , in agreement with increased oxidative stress in patients with POAG. Mitochondrial energetic substrates were also noted in several of the studies, indicating dysregulated energy metabolism in patients with POAG ( Leruez et al, 2018 ; Kouassi Nzoughet et al, 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…Among these studies, some changes were found to be common in several reports and share similar or overlapping metabolic pathways. For instance, significant upregulation of the metabolites in responding to oxidative stress was reported in both studies by Buisset et al (2019) and Takayanagi et al (2020) , in agreement with increased oxidative stress in patients with POAG. Mitochondrial energetic substrates were also noted in several of the studies, indicating dysregulated energy metabolism in patients with POAG ( Leruez et al, 2018 ; Kouassi Nzoughet et al, 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…With respect to pathophysiological mechanisms, oxidative stress plays an important role in the development of glaucoma. Takayanagi et al [121] explored the association between systemic and local oxidative stresses in POAG and PEXG by utilizing a metabolomics approach. They drew a conclusion that a low level of systemic antioxidant capacity was observed, along with up-regulation of antioxidant enzymes in aqueous humor, suggesting elevated oxidative stress in eyes with POAG, particularly in PEXG.…”
Section: Glaucomamentioning
confidence: 99%
“…ROS is mainly generated by the metabolism of the mitochondria and neutralized by antioxidants [ 15 ]. We previously reported that lower levels of serum biologic antioxidant potential were correlated with higher levels of IOP and with greater visual field loss in primary open-angle glaucoma (PG) [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing research program directed toward the analysis of the relationship between ophthalmologic disorders and stress markers measured by fingertip measurements [ 16 , 17 , 18 ], we investigated the clinical factors including SC and AGEs levels with glaucoma types. We previously reported AGEs levels in PG and EG [ 40 ]; however, the relationship between SC levels and glaucoma has not been reported.…”
Section: Introductionmentioning
confidence: 99%